Improved contractile potential in detrusor microtissues from pediatric patients with end stage lower urinary tract dysfunction - Gerwinn, Tim; Salemi, Souzan; Schori, Larissa J.; Planta, Dafni; Eberli, Daniel; Horst, Maya (Frontiers in Cell and Developmental Biology, 2022)
Autologous cell-based tissue engineering has been proposed as a treatment option for end stage lower urinary tract dysfunction (ESLUTD). However, it is generally accepted that cells isolated from patient bladders retain the pathological properties of their tissue of origin and therefore need to be improved before they can serve as a cell source for tissue engineering applications. We hypothesize that human three-dimensional (3D) microtissues of detrusor smooth muscle cells (SMCs) are valuable ex vivo disease models and potent building blocks for bladder tissue engineering. Detrusor SMCs isolated from bladder wall biopsies of pediatric ESLUTD patients and healthy controls were expanded and cultured into 3D microtissues. Gene and protein analyses were performed to explore the effect of microtissue formation on SMC viability, contractile potential, bladder wall specific extracellular matrix (ECM) composition and mediators of ECM remodeling. Through microtissue formation, remodeling and intensified cell-cell interactions, the ESLUTD SMCs lost their characteristic disease phenotype. These microtissues exhibited similar patterns of smooth muscle related contractile proteins and essential bladder wall-specific ECM components as microtissues from healthy control subjects. Thus, the presented data suggest improved contractile potential and ECM composition in detrusor SMC microtissues from pediatric ESLUTD patients. These findings are of great relevance, as 3D detrusor SMC microtissues might be an appropriate cell source for autologous cell-based bladder tissue engineering.